BIOPOLYMER-BASED FILM PREPARATION FOR POTENTIAL SMART FOOD PACKAGING MATERIAL APLLICATION - Barleany, Dhena Ria; Sari, D K; Lestari, R S; Raharja, Y; Gunawan, A (Universitas Mercu Buana, 2023)
Public interest in colorimetric films for food freshness monitoring has increased recently. In addition to extending the shelf life of packaged food products, packaging materials are also required to provide current information about the freshness of the food while ensuring food quality and safety. The current work aims to prepare smart biodegradable films based on biopolymer-containing color indicators to monitor the quality of Decapterus spp. The pH-sensing colorimetric film was developed from a chitosan biopolymer modified using polyvinyl alcohol (PVA) and glycerol, as well as methyl red, as an indicator of fish freshness. The effect of using PVA and stirring conditions (temperature and time) on film production was evaluated on its physical appearance, water vapor permeability, and mechanical properties. The results show that the use of PVA can increase the transparency of chitosan films. Incorporating PVA into the film results in brighter and clearer colors compared to films without PVA. The temperature used in the preparation of the film solution has an influence on the mechanical properties and the water vapor permeability. The increasing stirring temperature leads to the enhancement of Young's modulus and the barrier properties against water vapor and moisture, still concurrently impacting a decrease in the film's yield strength and strain. Additionally, the film also exhibits responsiveness to pH during fish spoilage, with a color change that occurs from pink to yellowish. This confirms that the pH-responsive film resulting from this research has great potential to be applied as a real-time indicator of fish freshness during storage.